Identification of Learning Outcomes for Natural and Social Sciences Subjects on Plant Body Parts for Elementary School Students - Iksan, Muhamad (Program Studi Pendidikan Guru Sekolah Dasar Universitas Muhammadiyah Buton, 2024)
Identification of learning outcomes of Natural and Social Sciences subjects on the material